2010
DOI: 10.1590/s0037-86822010000400005
|View full text |Cite
|
Sign up to set email alerts
|

Level of behavior and knowledge concerning human papillomavirus among university students of a nursing college

Abstract: Introduction: Human pappilomavirus is one of the most common sexually transmitted diseases, and persistent HPV infection is considered the most important cause of cervical cancer. It is detected in more than 98% of this type of cancer. This study aimed to determine the level of knowledge concerning human papillomavirus among nursing college students of a private educational institution located in the City of Bauru, SP, and correlate their knowledge according to the course year. Methods: A descriptive study wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
6
0
3
Order By: Relevance
“…In Juraskova and collegious study (2011) conducted with psychology students, 45% were reported to have knowledge of HPV infection. In contrast to these studies, Cirilo et al (2010) found, in their study on nursing students, that 45% of first year students had knowledge of HPV infections, while 100% of the upper class students had knowledge of the disease (Cirilo et al, 2010;Juraskova et al, 2011). Similarly, in Greece study on midwives and midwifery students, a large percentage (90%) of the midwifery students were identified as having knowledge of HPV infection, while 58.6% were identified as having knowledge of the HPV vaccine (Dinas et al, 2009) According to the our and similar study findings (with a few exceptions), the level of knowledge among midwifery students HPV infection and HPV vaccination is insufficient.…”
Section: Determination Of the Knowledge Of Midwifery Students About Hmentioning
confidence: 81%
“…In Juraskova and collegious study (2011) conducted with psychology students, 45% were reported to have knowledge of HPV infection. In contrast to these studies, Cirilo et al (2010) found, in their study on nursing students, that 45% of first year students had knowledge of HPV infections, while 100% of the upper class students had knowledge of the disease (Cirilo et al, 2010;Juraskova et al, 2011). Similarly, in Greece study on midwives and midwifery students, a large percentage (90%) of the midwifery students were identified as having knowledge of HPV infection, while 58.6% were identified as having knowledge of the HPV vaccine (Dinas et al, 2009) According to the our and similar study findings (with a few exceptions), the level of knowledge among midwifery students HPV infection and HPV vaccination is insufficient.…”
Section: Determination Of the Knowledge Of Midwifery Students About Hmentioning
confidence: 81%
“…R. Sandfort & A. Pleasant, 2009) few have assessed this knowledge in men (Cirilo, Barbosa, & Zambrano, 2010; McPartland et al, 2005). Furthermore, little is known about the Hispanic student’s knowledge and beliefs about cervical cancer and HPV infection.…”
Section: Discussionmentioning
confidence: 99%
“…The performance of the students from the 1st year was lower than expected with an average of 9.9 correct answers, which may represent the low level of information acquired on the subject in elementary and high school which will only be addressed after the first year of graduate education (12) . Regarding the analysis of blocks of question, the block that had the highest percentage of correct totals in both classes was the "Benefits and Social Aspects" which are themes that have been already presented to students since the 1st year of the researched graduate course.…”
Section: Discussionmentioning
confidence: 68%